INDIRECT IMPLICATIONS OF SHARENTING ON THE NATIONAL SECURITY OF THE REPUBLIC OF SERBIA - Stjepanović, Bogdana M; Đurašević, Srđana (The Policy of National Security, 2026)
The global phenomenon of “sharenting”, defined as the extensive online sharing of minors’ personal data by parents, represents a complex and indirect threat to national security. Although the motives behind this practice are predominantly uncritical, it results in the construction of permanent digital identities for future generations without their prior consent. In the Republic of Serbia, digital risks are further exacerbated by the disparity between youth’s high digital engagement and parents’ limited knowledge of information security. While direct consequences, such as identity theft, are well-documented, this paper argues that aggregated data derived from sharenting serves as a strategic intelligence resource for both state and non-state actors. The systemic accumulation of this information facilitates sophisticated psychological profiling, extensive surveillance, and targeted influence operations, potentially compromising key state personnel and undermining social cohesion. Current vulnerabilities in the national cybersecurity system, coupled with legislative implementation challenges, create an environment that is highly conducive to such data exploitation. Addressing these threats requires a coordinated strategic approach that integrates strengthening legal frameworks, technical protection of critical infrastructure, and systemic digital education. Mitigating the risks arising from sharenting is not merely a child protection measure but an essential step in safeguarding national security.